Kelimpahan spesies asing invasif teklan (Ageratina riparia (Regel) R. M. King & H. Rob.: Asteraceae) pada vegetasi lantai di Kebun Raya “Eka Karya” Bali - Tirta Sari, Dewa Ayu Intan; Wijaya, I Made Saka; Sutomo, Sutomo (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i02.p04, 2022)
Ageratina riparia is an invasive alien species that get a particular attention in “Eka Karya” Bali Botanical Garden. This study aims to determine the abundance of invasive alien species A . riparia on forest floor vegetation in “Eka Karya” Bali Botanical Garden, and the factors that influence its abundance. Ageratina riparia is an invasive herb that can disrupt the balance of the ecosystem. The advantages of this plant in reproducing and adapting to the environment, make this plant very easy to grow and develop in a habitat. The purposive sampling method was used with the plot that placed systematically. The research area divided into five research stations with 10 plots (2 x 2 m) for each station. Vegetation data were analyzed to determine the density, relative density, frequency, relative frequency, and important value index (INP), then completed with Shannon-Weiner diversity index (H'), dominancy index (C), evenness index (E) and visualization abundance of species A . riparia of with Non-metric Multi Dimensional Scaling (NMDS). Environmental data is calculated analyses in Detrended Correspondence Analysis (DCA). The results showed that A . riparia at station 1 (Kawasan Kepala Burung) had an INP of 62.50%, station 2 (Taman Usada) with an INP of 52.40%, station 3 (Taman Cyathea) with an INP of 89.09%, station 4 (middle open area) with an INP of 110.25%, and the highest is at station 5 (Taman Upacara Panca Yadnya) with an INP value of 118.92%. The presence of A . riparia can be influenced by all environmental factors measured such as air humidity, soil moisture, soil pH, air temperature and soil temperature, altitude, land slope, and light intensity.